GENDER REPRESENTATION IN CONTEMPORARY ENGLISH LANGUAGE TEXTBOOKS - Isabella Romano (International Journal of Literature and Language Studies, 2026)
This article investigates gender representation in contemporary English language textbooks within the broader field of linguistics and applied language studies. The study uses six widely used intermediate-level English textbooks, including reading passages, dialogues, images captions, and activity instructions and applies critical discourse analysis combined with frequency counts of roles, occupations, and speaking turns. The main finding is that male and female characters appeared in more balanced numbers than in older materials, but occupational and emotional stereotypes still remained visible. The article argues that textbook evaluation should consider both numerical balance and the quality of social roles assigned to characters. The discussion is relevant to researchers, teachers, curriculum designers, and graduate students who need concise but systematic models of linguistic inquiry.